(untitled) (Revista Venezolana de Salud Pública, 2020)
The objective was to describe the responsibility in the diagnosis of the patient with cerebrovascular accident in the General Hospital Guasmo Sur. The design was qualitative and interpretive. The method was chosen because this way we can describe the problem based on the participant’s opinion and perspective in relation to their experiences. The key informants were four people; between resident doctors and medical interns who work in the study hospital; Open interviews were carried out as a data collection technique, which were recorded in audio and transcribed so that each of the participants could then review and approve it to proceed with the study. Scientific rigor was also carried out through informed consent and ethical considerations. The results are analyzed through the construction of categories and codes, for the formation of the theoretical approach. It was concluded that the responsibility in the diagnosis and treatment of the patient with cerebrovascular accident in the General Hospital Guasmo sur is evidenced by a lack of protocols of action and ignorance of this, by the lack of commitment, interest and a negative attitude on the part of the health personnel; And to this is added poor organizational management that does not provide the necessary support to your health team.